Assessing the physical and chemical properties of 15year old normal and coppiced teak (Tectona grandis) woods for their effective utilization - Dwumaa, Harriet (2017)
A thesis submitted to the Department of Wood Science and Technology Kwame Nkrumah University of Science and Technology In partial fulfillment of the requirements for the degree of Master of Science,